Implementasi Perma Nomor 2 Tahun 2012 Tentang Penyesuaian Batasan Tindak Pidana Ringan Dan Jumlah Denda Dalam KUHP - Ahmad Yusril Nasution; Nurida Situmeang; Dedy Suhendra (UM.Tapanuli Selatan, 2025)
In the Criminal Code, crimes categorized as minor crimes are crimes where the value of the stolen goods is not more than Rp250,- and are subject to a maximum imprisonment of 3 months. PERMA Number 02 of 2012 contains the Adjustment of the Limits of Minor Crimes and the Amount of Fines in the Criminal Code. The research method used is empirical legal research. The results of the study indicate that judges in deciding minor criminal cases are in accordance with PERMA Number 02 of 2012 by considering the aggravating and mitigating factors for the defendant.